The resilience of youth entrepreneur: the role of social capital, financial literacy, and emotional intelligence on SMEs’ performance in Indonesia - Worokinasih, Saparila; Nuzula, Nila Firdausi; Damayanti, Cacik Rut; Sirivanh, Thongvanh (BISMA (Bisnis dan Manajemen), 2023)
This paper aims to investigate factors that contribute to strengthening the business performance of youth entrepreneurs. Based on the Resource-Based Theory (RBV), this study examines the social capital, financial literacy, and emotional intelligence of small and medium-sized business (SME) youth owners' effect on business performance. The link between the variables is evaluated using the Partial Least Square – Structural Equation Modelling (PLS-SEM). The findings demonstrated that youth entrepreneurs' social capital and financial literacy positively and significantly affect emotional intelligence. At the same time, SME performance was directly influenced by the youth owner's emotional intelligence. Based on the research, SME youth owners are urged to strengthen their emotional intelligence to make prudent business choices that would significantly enhance their firm's success. Also, maintaining the relationship and upgrading their financial literacy could indirectly enhance business performance. Managers in SMEs must understand the link between social capital, financial literacy, and emotional intelligence to improve performance. Cultivating strong business networks and relationships, ensuring sound financial practices, and fostering emotionally intelligent leadership can drive stronger business performance and maintain a competitive advantage.